Self-assembled chlorophyll a systems as studied by californium-252 plasma desorption mass spectroscopy - Hunt, J. E. (1980)
Self-assembled chlorophyll a and pheophytin a systems in thin solid films have been studied by (252)Cf plasma desorption mass spectrometry (PDMS). The (252)Cf-PDMS spectra of these films show monomer cation and anion molecular ions, ions of molecular aggregates, and positive and negative ion fragmentation patterns arising from the loss of various aliphatic side chains from the chlorin ring. Chlorophyll a films cast from dry carbon tetrachloride solution, in which chlorophyll a is known to occur as the dimer, produced an abundant dimer ion. The highest degree of chlorophyll a self-assembly was observed in chlorophyll a films cast from n-octane solutions. Oligomer ions extending upwards in size to the heptamer were detected in this system.